Segmented Compression Molding for Composite Manufacture - Chang, Chih-Yuan (Proceedings of Engineering and Technology Innovation, 2017)
In the present study a new technique of vacuum assisted resin transfer molding (VARTM), called segmented compression molding (SCM), is proposed to improve filling process. In the method, a double-bag is placed between the upper mold and the cavity, and each bag is controlled individually. Through the vacuum pulling the double-bag upward, resin is easily infused into the loose preform. After the completion of resin infusion, the resin inlet is closed. The vacuum on the bags are sequentially released to atmospheric pressure, the inflated bags squeeze the surplus resin from the wetted preform toward dry loose preform and the filling process is thus reduced. This study is to introduce the SCM, model the filling process and explore the surface quality of the SCM parts. Results show that the SCM filling process is decreased by using a high initial cavity thickness. As compared with transfer resin transfer molding (RTM) and typical VARTM, SCM can reduce the filling process in the work. The surface roughness of SCM part approximates that of VARTM, but it is much inferior to that of RTM.